PENGARUH ABSORPTIVE CAPACITY TERHADAP EFEKTIFITAS TRANSFER TEKNOLOGI, SEBUAH STUDI EMPIRIS PADA PERUSAHAAN VAKSIN DI BANDUNG, INDONESIA - Suhartono, Undi; Samryn, L.M.; Budiantoro, Anandha (Management and Leadership Study Programme, 2024)
Absorption capacity is a variable that has been proven to influence the effectiveness of transfer technology in previous studies. Few of these studies examined this variable in the vaccine industry sector. This research is an empirical study to see the effect of absorption and each of its constituent dimensions (the ability to recognize, the ability to acquire, the ability to assimilate, and the ability to apply) to technology transfer effectiveness carried out in vaccine companies. The research approach is proportional stratified random sampling, where the data is processed statistically quantitatively. Research data were collected by distributing questionnaires containing 43 questions to 114 respondents from employees with strategic position levels in the vaccine companies studied. Quantitative statistical methods with SPSS software were used to analyze the research data, including regression analysis, Pearson Product Moment correlation analysis, and impact analysis. The results showed that the level of absorption capacity of the vaccine companies studied had a statistically significant positive effect on the technology transfer's effectiveness. Each dimension of absorptive capacity is separately proven to have a statistically significant positive impact on the effectiveness of technology transfer in the order from which it gives the most significant influence, namely the ability to apply, the ability to assimilate, the ability to recognize, and the ability to acquire. The findings in this study can be used as a reference by company stakeholders as a basis for maintaining and increasing their absorption capacity based on the order of magnitude of influence from each dimension studied to increase the effectiveness of technology transfer in the future.